Transcatheter or surgical treatment of aortic-valve stenosis - Blankenberg, Stefan; Seiffert, Moritz; Vonthein, Reinhard; Baumgartner, Helmut; Bleiziffer, Sabine; Borger, Michael A.; Choi, Yeong-Hoon; Clemmensen, Peter; Cremer, Jochen; Czerny, Martin; Diercks, Nina; Eitel, Ingo; et al. (The New England journal of medicine, 2024)
A randomized trial that enrolled patients with severe aortic stenosis at low or intermediate surgical risk showed that transcatheter aortic-valve implantation was noninferior to surgical aortic-valve replacement at 1 year.
Online veröffentlicht: 8. April 2024
Gesehen am 12.11.2024